2017
DOI: 10.1001/jama.2017.4078
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Accuracy of Physician and Nurse Predictions for Survival and Functional Outcomes 6 Months After an ICU Admission

Abstract: ICU physicians' and nurses' discriminative accuracy in predicting 6-month outcomes of critically ill patients varied depending on the outcome being predicted and confidence of the predictors. Further research is needed to better understand how clinicians derive prognostic estimates of long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
117
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 37 publications
4
117
0
Order By: Relevance
“…This result can be considered in agreement with several studies on different medical issues showing that predictor's confidence correlates very well with the correctness of the prediction ( Detsky et al , 2017; Hautz et al , 2015; Kämmer et al , 2017; Kurvers et al , 2016). Indeed, the concordance of different members of a given group (students or runs of the random forest model) can be taken as indicating that the agent is "sure" of the forecast.…”
Section: Discussionsupporting
confidence: 92%
“…This result can be considered in agreement with several studies on different medical issues showing that predictor's confidence correlates very well with the correctness of the prediction ( Detsky et al , 2017; Hautz et al , 2015; Kämmer et al , 2017; Kurvers et al , 2016). Indeed, the concordance of different members of a given group (students or runs of the random forest model) can be taken as indicating that the agent is "sure" of the forecast.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the study by Detsky et al [16], clinicians in our study were not explicitly expected to provide prognostic estimates about the patients’ outcomes. We preferred to focus on the intuitive-heuristic more than the analytic-deductive part of the complex ethical decision-making process [26, 27], by asking clinicians whether they felt that the care provided to their patient on a specific day was consistent with the expected outcome in terms of survival and quality of life, and whether this amount of care was in line with the patient’s or relatives’ wishes.…”
Section: Discussionmentioning
confidence: 71%
“…In addition to enhancing trust and cohesion in a team, such a climate may also reduce uncertainty in decision-makers by favoring intra- and interdisciplinary transfer of knowledge, experience and values [14]. Several studies have already shown that concordant prognostic estimates [15, 16] or perceptions of inappropriate [17] or futile care [18] by two clinicians may be considerably more predictive about the patient’s short- and long-term outcomes than usually thought. However, whether the quality of the ethical climate prevailing in a unit further improves the identification of patients receiving excessive care, and impacts on patient outcomes and written treatment-limitation decision (TLD), is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are ideally suited to improve patient and family care at the end of life. Their physical presence at the bedside and training in symptom management and palliation position them to directly attend to and oversee the care of dying patients . In fact, bereaved family members say their loved one's treatment preferences were respected and concerns listened to when nurses were involved in end‐of‐life care and decision making .…”
mentioning
confidence: 99%
“…Their physical presence at the bedside and training in symptom management and palliation position them to directly attend to and oversee the care of dying patients. 17,18 In fact, bereaved family members say their loved one's treatment preferences were respected and concerns listened to when nurses were involved in end-of-life care and decision making. 19 Despite nurses' proximity to patients and their clinical skill set, they remain an untapped resource because of the constraints and demands of their practice environments.…”
mentioning
confidence: 99%